Assessing the Effectiveness of Online Teaching Methodology among Emergency Medical Professionals in Pune, India - Parag Rishipathak1, Monesh Bhandari2 , Anand Hinduja3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction: With rapid evolution of information and research in Healthcare, students find it verychallenging to keep pace with the latest knowledge. To overcome this challenge, Healthcare InformationTechnology should be implemented at multiple levels i.e. during their Under Graduate and Post-Graduatetraining which shall make them well versed with online learning. During the COVID-19 pandemic manyhealthcare institutions have adapted to online teaching methodology, to continue with the academic year butit is necessary to assess the effectiveness and impact on students.In developing countries, where efficient educators in Healthcare are less in number, adapting to online basedcurriculum shall increase the reach of Healthcare Education to maximum learners.Objective: To assess the effectiveness of online teaching methodology among Emergency MedicalProfessionalsMethodology: The study was conducted amongst 100 Emergency Medical Professionals in Pune, India. Anonline session on Basic Life Support and Emergency Medical Services protocols was conducted via Zoomapplication. Participants were asked to respond to a pretested and validated tool, the Student Evaluation ofOnline Teaching Effectiveness (SEOTE).Result and Discussion: Online teaching was introduced in most of the universities as an alternative toclassroom training due to the COVID 19 pandemic. The study is an unique attempt to assess the participantfeedback on the effectiveness of a single online session. The results clearly demonstrate that majority of theparticipants provided a very positive feedback of the online teaching session.Conclusion: The participants’ feedback with regard to online teaching was found to be highly encouraging.Further longitudinal studies are essential to gauge the impactfulness of online teaching as an alternativemodality to classroom instruction.